Ways to increase the attractiveness of education in colleges in Kazakhstan (on the example of the Mangystau region) - Tuleuov Тулеуов А.Ж.; Muhamedzhanova Мухамеджанова А.Г. (Рroblems of engineering and professional education, 2022)
Based on an extensive statistical analysis of educational institutions of various forms of ownership and in-depth interviews with the heads of educational organizations, the authors cite the reasons for the low interest in training in vocational education organizations and the low reputation of educational organizations and suggest solutions to increase them. Secondary vocational education is of key importance for the innovative development of any country.Head of State Kassym-Jomart Tokayev has repeatedly noted in his Address to the people of Kazakhstan the importance of education, including secondary vocational and technical education. The article deals with the need for reforms in the education system, taking into account globalization. The main direction of the development of secondary vocational education in the Republic of Kazakhstan is the introduction of a two-level system of professional training: secondary specialized-bachelor’s degree, based on the successful experience of the United States.